PENERAPAN PROSEDUR PURCHASING DAN RECEIVING PADA HOTEL BINTANG 5 DI KABUPATEN BADUNG - Arista, Komang Cintiya; Sumariati, I Dewa Ayu Rai; Rukmiyati, Ni Made Sri (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The hotel industry is a sector that provides accommodation, as well as food and beverage services. Hotel management must carefully consider the raw materials used to ensure the quality of the food products offered to guests. The procurement of raw materials used by hotels begins with the inventory of food and beverages, encompassing activities related to the purchasing and receiving of goods. The aim of this research is to examine the implementation of purchasing and receiving procedures at five-star hotels in Badung Regency. This study employs a qualitative descriptive data analysis technique, gathering data through questionnaires distributed to staff members working in the purchasing and receiving departments of five-star hotels in Badung Regency. The findings of this study indicate that there are variations in the implementation of purchasing and receiving procedures among five-star hotels in Badung Regency. Additionally, the study reveals innovations in the supplier selection process, as several five-star hotels in Badung Regency have begun to implement sustainability purchasing and cluster purchasing in recent years. This study does not provide a detailed discussion of sustainability purchasing and cluster purchasing, thereby presenting an opportunity for future research to explore these topics further.